The Heidelberg inventory of geographic system competency model - Viehrig, Kathrin; Siegmund, Alexander; Funke, Joachim (Competence assessment in education, 2017)
The concept “system” is fundamental to many disciplines. It has an especially prominent place in geography education, in which additionally, the spatial perspective is central. Empirically validated competency models dealing specifically with geographic systems - as well as adequate measurement instruments - are still lacking. Therefore, based on the theoretically-guided development of a Geographic System Competency (GSC) model, the aim was to build and evaluate such a measurement instrument, with the help of probabilistic measurement models. The competency model had three dimensions: (1) “comprehend and analyze systems”, (2) “act towards systems” and (3) “spatial thinking”, whereby dimension (2) was changed to “evaluating possibilities to act towards systems” after a thinking-aloud study. A Cognitive Lab (CogLab) and two quantitative studies (Q1 n = 110, Q2 n = 324) showed divergent results. Dimension (2) could not be identified in both quantitative studies. Whereas Dimensions (1) and (3) constituted separate dimensions in Q1, in Q2 the two-dimensional model did not fit significantly better than the one-dimensional model. Besides showing the close relationship between spatial and systemic thinking in geographic contexts, which are thus both needed in modeling GSC, the project highlights the need for more research in this central area of geography education.